Pengaruh Brand Awareness Safi White Natural Terhadap Keputusan Pembelian: Survei Pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Jakarta Angkatan 2021-2022 - Dea Zhafira Widya Ningsih; Aminah Swarnawati (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effect of brand awareness on purchasing decisions for Safi White Natural products among female Communication Science students of Universitas Muhammadiyah Jakarta, batch 2021-2022. This study uses a survey method to collect data from respondents. The population in this study were all female Communication Science students of UMJ, batch 2021-2022, with a sample of 77 respondents taken using simple random sampling techniques and calculated using the Slovin formula. The results showed that the level of brand awareness of Safi White Natural was in the high category, with an average value of 3.52 on the Likert scale. Respondents stated that they recognized Safi products through various media, including social media, television advertisements, and personal usage experiences. In addition, purchasing decisions showed good results, with an average value of 3.50, where the majority of respondents considered Safi products to be in accordance with their skincare needs. Simple linear regression analysis showed that brand awareness had a significant influence on purchasing decisions, with a correlation coefficient value (